Healthcare transition in pediatric liver transplantation: The perspectives of pediatric and adult healthcare professionals. (26th June 2019) - Wright, Jessica; Elwell, Laura; McDonagh, Janet; Kelly, Deirdre; McClean, Patricia; Ferguson, James; Wray, Jo
Abstract: Introduction: Transition from pediatric to adult services of young people with a liver transplant is an important priority due to increasing numbers of young people surviving into adulthood. There is increased incidence of graft loss and non‐adherence following transfer to adult services. Although studies have considered the views and perceptions of young people who have undergone liver transplantation and their parents about transition, there is currently no qualitative research with healthcare professionals working in the field of liver transplantation. The aim of this study was to elicit the views of this group of stakeholders about barriers and facilitators of an effective transition process. Methods: Semi‐structured interviews were carried out with 11 HCPs from pediatric and adult liver transplant programs and from a range of professional backgrounds. Interviews were transcribed verbatim and analyzed using thematic analysis. Results: Four themes were identified: "non‐adherence and psychosocial issues, " "need for better psychological support, " "the role of parents, " and "the emotional impact of transition on healthcare professionals." Within these themes, professionals described factors which hindered or promoted an effective transition process. Conclusions: Screening tools which address psychological and social aspects of the lives of young people should be used in routine practice to identify patients requiring psychosocial support and to identify those at risk of non‐adherence. All staff involved with transition should be trained in the use of psychosocial screening strategies. The development of a formal referral pathway so that young people can access psychological support in adult services is recommended.